Estudio de la adición de las fibras linaza (Linum usitatissimum) y salvado de trigo (Triticum aestivum), en la elaboración de yogurt de soya (Glycine max) de tres sabores taxo (Passiflora tripartita), mora (Rubus glaucus) y guanábana (Annona muricata), en el laboratorio académico de lácteos de la carrera de ingeniería agroindustrial, en el período 2014-2015 - Guaña Guaña, Edwin Rolando (2015)
Contributing innovative ideas for the food industry and knowing that at present it is considering to soy for its high nutritional content for the production of different products has considered developing a different variety of yogurt soy, such research is It took place at the Academic Laboratory Dairy Race Agroindustrial Engineering, in which the study of the addition of flax fiber (Linum usitatissimum) and wheat bran (Triticum aestivum), in developing soy yogurt (glycine max) three flavors taxo, blackberry and soursop. For the purpose of this investigation the design completely randomized Boques (DBCA) and subsequently Tukey test at 5% significance was used to determine the best treatments obtained by sensory analysis, the amount of yogurt that was used for each of the treatment is the same 1 liter was added to 10 g.